PERENCANAAN TEBAL PERKERASAN KAKU JALAN RAYA CADAS - KUKUN KABUPATEN TANGERANG: -- - andri arthono (IONTech Journal, 2023)
ABSTRACT Portland cement concrete pavement or more commonly called rigid pavement or Rigid Pavement, consists of a Portland cement concrete slab and a foundation layer (may or may not exist) on the subgrade. This concrete slab can use reinforcement or without reinforcement depending on the planning. This is different from flexible pavements where the stiffness of the pavement is obtained from the thickness of the subbase layers, the foundation and the surface layer. Because the most important thing is to know the load-bearing capacity of the structure, the factor that needs to be considered in designing concrete road pavements is the strength of the concrete itself. The varying strength of the subgrade or foundation has little effect on the structural capacity of the pavement (the thickness of the concrete slab). The subbase layer, if used under a concrete slab, is intended as a working floor and for drainage to prevent pumping. Pumping is the event of the release of water accompanied by subgrade grains through joints and cracks or on the pavement edge, due to deflection or vertical movement of the concrete plate due to traffic loads, after free water has accumulated under the concrete plate. Pumping can cause cavities to occur. under the concrete plate causing damage or cracks to the plate Key words: Rigid Pavement,Semen Portland,Pekerasan Lentur , Pumping.